Loss-of-function screening to identify miRNAs involved in senescence: tumor suppressor activity of miRNA-335 and its new target CARF - Yu, Yue (Sci Rep, 2016)
Significance of microRNAs (miRs), small non-coding molecules, has been implicated in a variety of biological processes. Here, we recruited retroviral insertional mutagenesis to obtain induction of an arbitrary noncoding RNAs, and coupled it with a cell based loss-of-function (5-Aza-2′-deoxycytidine (5Aza-dC)-induced senescence bypass) screening system. Cells that escaped 5-Aza-dC-induced senescence were subjected to miR-microarray analysis with respect to the untreated control. We identified miR-335 as one of the upregulated miRs. In order to characterize the functional significance, we overexpressed miR-335 in human cancer cells and found that it caused growth suppression. We demonstrate that the latter accounted for inhibition of 5-Aza-dC incorporation into the cell genome, enabling them to escape from induction of senescence. We also report that CARF (Collaborator of ARF) is a new target of miR-335 that regulates its growth suppressor function by complex crosstalk with other proteins including p16(INK4A), pRB, HDM2 and p21(WAF1).